(untitled) (Research, Society and Development, 2020)
The new coronavirus (SARS-CoV-2) is from the subfamily Betacoronavirus, highly pathogenic and responsible for causing severe acute respiratory syndrome. It can be transmitted by interpersonal contact through the inhalation of contaminated droplets, or by indirect contact with a contaminated surface. The dental office can be a place of potential contamination by the spread of aerosol containing saliva/blood, in addition to very close contact with the professional and equipment. The incubation period of the virus can reach more than six days, and the manifestation of the disease can include fever, cough, nausea, vomiting, diarrhea, headache, muscle pain, among other symptoms; laboratory tests demonstrate lymphocytopenia, leukopenia and increased C-reactive protein. Measures to protect against the contamination of the new coronavirus are necessary even in patients who have no symptoms. During the period of social distance proposed as a method to prevent the spread of the virus, the dental surgeon must incorporate extra care in preventing the spread of the disease, using personal protective equipment and cleaning the equipment and the environment in an appropriate manner. study was to carry out a literature review on dental care during the COVID-19 pandemic period. In this way, it is up to everyone to follow the pre-established preventive protocols, aim for diagnostic methods that are more accessible to the general population and wait for an effective immunization system.